Machine learning-driven identification of multi-targeted lead compounds among 5,6-dihydrotetrazolo[1,5-c]quinazolines for neurodegenerative and neglected tropical diseases - Antypenko, L. M.; Antypenko, O. M.; Антипенко, Олексій Миколайович (My University, 2024)
In the rapidly advancing field of drug discovery and development, computational methods have become indispensable tools for accelerating the identification and optimization of potential drug candidates.
Keywords: тези доповідей